1997
DOI: 10.1126/science.275.5299.502
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Exchanges of Energy, Water, and Carbon Between Continents and the Atmosphere

Abstract: Atmospheric general circulation models used for climate simulation and weather forecasting require the fluxes of radiation, heat, water vapor, and momentum across the land-atmosphere interface to be specified. These fluxes are calculated by submodels called land surface parameterizations. Over the last 20 years, these parameterizations have evolved from simple, unrealistic schemes into credible representations of the global soil-vegetation-atmosphere transfer system as advances in plant physiological and hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
852
0
22

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,361 publications
(879 citation statements)
references
References 67 publications
5
852
0
22
Order By: Relevance
“…However, until recently, most modern land surface models (i.e., second-or third-generation models; Sellers et al 1997) have not formally included urban parameterizations. Masson (2006) classifies urban parameterizations in three general categories: 1) empirical models; 2) vegetation models, with and without drag terms, adapted to include an urban canopy; and 3) single-layer and multilayer models that include a threedimensional representation of the urban canopy.…”
Section: Introductionmentioning
confidence: 99%
“…However, until recently, most modern land surface models (i.e., second-or third-generation models; Sellers et al 1997) have not formally included urban parameterizations. Masson (2006) classifies urban parameterizations in three general categories: 1) empirical models; 2) vegetation models, with and without drag terms, adapted to include an urban canopy; and 3) single-layer and multilayer models that include a threedimensional representation of the urban canopy.…”
Section: Introductionmentioning
confidence: 99%
“…The algorithms within the model that represent physiological processes such as photosynthesis and respiration also reflect a large body of field and laboratory ecophysiological research (Sellers, Dickinson et al, 1997). LAI is well recognized as an important control on GPP/NPP in boreal and temperate forests (Bonan, 1993;Woodward, 1987) and it is often prescribed in process model applications (Hunt et al, 1996;Williams et al, 2001).…”
Section: Assessment Of Bigfoot Gpp Productsmentioning
confidence: 99%
“…LAI and FPAR are parameters that are descriptive of vegetation canopy structure and its energy absorption capacity, and are key state variables in most ecosystem productivity models and in global models of climate, hydrology, and ecology (Sellers et al, 1997). For example, Buermann et al (2001) reported that the use of satellite LAI reduces the model biases in near-surface air temperature in comparison to observations.…”
Section: Partitioning Of Solar Radiationmentioning
confidence: 99%
“…The MISR team is responsible for development and validation of algorithms and for producing a series of products which include vegetation green Leaf Area Index (LAI) and Fraction of Photosynthetically Active Radiation (400-700 nm) absorbed by vegetation (FPAR). These products are required to describe the exchange of fluxes of energy, mass (e.g., water and CO 2 ) and momentum between the surface and atmosphere (Sellers et al, 1997).…”
Section: Introductionmentioning
confidence: 99%